Nanotechnology applied to pharmaceutical technology - Rai, Mahendra; Santos, Carolina Alves dos (Springer, 2017)
Highly-experienced nanotech researchers Rai and Alves dos Santos have gathered a truly international and interdiscplinary group of authors to contribute to this edited work on nanotechnology and how it applies to pharmaceutical technology. They keep the focus on devising innovative nanopharmaceutical products and solutions to treat such diseases as cancer, infections, eye diseases, and in tackling multi-drug resistance threats. Nanotechnology Applied to Pharmaceutical Technology consists of four sections that include coverage of biosynthesis of nanoparticles, nano-material based formulations and toxicity, and safety issues.